Maternal Serum Melatonin Increases During Pregnancy and Falls Immediately After Delivery Implicating the Placenta as a Major Source of Melatonin - Ejaz, Haroon; Figaro, Juliana K.; Woolner, Andrea M. F.; Thottakam, Bensita M. V.; Galley, Helen F. (Frontiers in Endocrinology, 2021)
Melatonin is a neuroendocrine hormone which regulates circadian rhythm and is also an antioxidant. The role of melatonin in pregnancy is emerging. The enzymes needed for endogenous synthesis of melatonin have been identified in the placenta, although the contribution to circulating maternal melatonin in normal pregnancy is unclear. This work aimed to determine serum levels of melatonin and its major metabolite 6-hydroxymelatonin sulfate (6-OHMS) in normal pregnant women during each trimester of pregnancy, and immediately after delivery. Blood samples were obtained from a cohort of healthy pregnant women during each trimester of pregnancy (n=26), from women scheduled for elective Cesarean section (CS) before and after delivery (n=15), along with placental samples, and from healthy non-pregnant women as controls (n=30). Melatonin and its major metabolite, 6-OHMS were measured using enzyme immunoassay. Levels of serum melatonin were significantly higher during pregnancy than in non-pregnant women (P=0.025) and increased throughout pregnancy (P<0.0001). In women undergoing CS, serum melatonin decreased markedly 24h after delivery (P=0.0013). Similar results were seen for serum levels of 6-OHMS, and placental tissue 6-OHMS levels correlated with week of gestation at delivery (p=0.018). In summary, maternal melatonin production is higher than in non-pregnant women, increases significantly during pregnancy with highest levels in the third trimester, and decreases abruptly after delivery. These results suggest that the placenta is a major source of melatonin and supports a physiological role for melatonin in pregnancy.